Unmasking the architecture of ant–diaspore networks in the Brazilian Savanna - Anjos, Diego; Dáttilo, Wesley; Del-Claro, Kleber (PloS one, 2018)
Ant-diaspore interactions are directly related to fruit consumption, seed predation and dispersal, being determinant for the plant fitness. However, although abundant and diversified, these ecological interactions have been neglected in network studies. Understanding the structure of these networks is the first step in preserving these ecological functions. However, describing the network structure is not enough; we need to understand what mechanisms are behind the network patterns. In this study, for the first time, we describe the structure of the ant-diaspore network, considering only the interactions that can benefit plants, separating it into fruit consumption and diaspore removal networks in the Brazilian Savanna. We postulated that ant-diaspore interactions tend to be more specialized in the diaspore removal network compared to the fruit consumption network. Furthermore, we tested whether morphological features, such as size of mandibles of ants and diaspores, could modulate these ecological networks. Overall, we recorded 24 ant and 29 plant species interacting. We found that fruit consumption and diaspore removal networks exhibited similar patterns of interactions (i.e., non-modular), although only the diaspore removal network was nested. The diaspore removal network did not show a more specialized pattern than the fruit consumption network, since both networks consisted of opportunistic interactions. We found that ant mandible and diaspore size does not explain the structure of ecological networks, but in diaspore removal networks the relationship between these morphological traits may explain the pattern of interactions. Thus, we showed that mandible size of ants may have implications on seedling recruitment, suggesting that mandible size can predict possible effects on plant fitness within in diaspore removal networks. Overall, ant-diaspore networks maintain important ecological functions, such as fruit consumption and seed dispersal, which often implies an increase in reproductive success of the plants.